Tiktok Sebagai Media Sosial Populer untuk Komunikasi Bisnis - Mutiara Apriliani Nur Zahra; Wuri Wulandari; Yegar Agnes Citra Widya (Syntax Idea)
The growth of the internet and the use of social media have made it easier for people to communicate and access information according to their needs. This ease of access is utilized by social media users not only as a means of information dissemination but also as a platform for personal identity expression, social integration and interaction, and entertainment. With the increasing number of social media users, a unique phenomenon has emerged in Indonesian society, namely the rise of online shopping on social media platforms, especially TikTok. This has made TikTok a popular social media platform for business communication, including promotional content. This research is conducted using observation and content analysis methods with the aim of analyzing the phenomenon of TikTok as a popular platform for business communication by analyzing the content of videos that relate to the business communication process. The study also relates this analysis to stimulus and response theories as well as decision-making theories in the context of purchasing decisions.